Microneutralization assay titres correlate with protection against seasonal influenza H1N1 and H3N2 in children. - Chris P Verschoor; Pardeep Singh; Margaret L Russell; Dawn M E Bowdish; Angela Brewer; Louis Cyr; Brian J Ward; Mark Loeb (PLoS ONE, 2015)
Although the microneutralization (MN) assay has been shown to be more sensitive than the hemagglutination inhibition (HAI) assay for the measurement of humoral immunity against influenza viruses, further evidence relating MN titres to protective efficacy against infection is needed. Serum antibodies against seasonal H1N1 and H3N2 influenza were measured in children and adolescents (n = 656) by MN and hemagglutination inhibition (HAI) assays. Compared to HAI, the MN assay is more sensitive in detecting serum antibodies and estimates of protective effectiveness against PCR-confirmed infection were higher for both subtypes. Given our findings, the MN assay warrants further consideration as a formal tool for the routine evaluation of vaccine-induced antibody responses.